Adhesion failure behavior of sputtered calcium phosphate thin film coatings evaluated using microscratch testing - Toque, Jay Arre; Herliansyah, Muhammad Kusumawan; Abd Shukor, Mohd Hamdi; Ide-Ektessabi, A.; Sopyan, Iis (Elsevier, 2010)
It is generally accepted that calcium phosphate (CaP) is one of the most important biomaterials in implant coating applications mainly because of its excellent bioactivity. However, its relatively poor mechanical properties limits its application. This entails that a better understanding of the mechanical properties of a CaP coating is a must especially its behavior and the mechanisms involved when subjected to stresses which eventually lead to failure. The mechanical properties of the coating may be evaluated in terms of its adhesion strength. In this study, a radio frequencymagnetron (RFMS) sputtering technique was used to deposit CaP thin films on 316L stainless steel (SS). The coatings were subjected to series of microscratch tests, taking careful note of its behavior as the load is applied. The adhesion behavior of the coatings showed varying responses. It was revealed that several coating processrelated factors such as thickness, postheat treatment and deposition parameters, to name a few, affect its scratching behavior. Scratch testingrelated factors (i.e. loading rate, scratch speed, scratch load, etc.) were also shown to influence the mechanisms involved in the coating adhesion failure. Evaluation of the load displacement graph combined with optical inspection of the scratch confirmed that several modes of failure occurred during the scratching process. These include trackside cracking, tensile cracking, radial cracking, buckling, delamination and combinations of one or more modes.